Knee joint neuromuscular activation performance during muscle damage and superimposed fatigue - Minshull, C.; Eston, R.; Rees, D.; Gleeson, N. (Journal of Sports Sciences, 2012)
This study examined the concurrent effects of exercise-induced muscle damage and superimposed acute fatigue on the neuromuscular activation performance of the knee flexors of nine males (age: 26.7±6.1 years; height 1.81±0.05 m; body mass 81.2±11.7 kg [mean±s]). Measures were obtained during three experimental conditions: (i) `fatigue-muscle damage`, involving acute fatiguing exercise performed on each assessment occasion plus a single episode of eccentric exercise performed on the first occasion and after the fatigue trial; (ii) `fatigue`, involving the fatiguing exercise only; and (iii) `control` consisting of no exercise. Assessments were performed prior to (pre) and at 1 h, 24 h, 48 h, 72 h, and 168 h relative to the muscle damaging eccentric exercise. Repeated-measures analyses of variance (ANOVAs) showed that muscle damage elicited reductions of up to 38%, 24% and 65% in volitional peak force, electromechanical delay and rate of force development compared to baseline and controls, respectively (F [10, 80] = 2.3 to 4.6; P < 0.05) with further impairments (6.2% to 30.7%) following acute fatigue (F [2, 16] = 4.3 to 9.1; P < 0.05). By contrast, magnetically-evoked electromechanical delay was not influenced by muscle damage and was improved during the superimposed acute fatigue (14%; F [2, 16] = 3.9; P < 0.05). The safeguarding of evoked muscle activation capability despite compromised volitional performance might reveal aspects of capabilities for emergency and protective responses during episodes of fatigue and antecedent muscle damaging exercise.